Cuprous oxide thin films for a photoelectrochemical cell of ITO/Cu 2O/PVC-LiClO 4/graphite - Dewi Suriyani, Che Halin; Ibrahim, Abu Talib, Prof. Dr.; Daud, Abd Razak; Muhammad Azmi, Abdul Hamid, Dr. (Trans Tech Publications Inc., 2013)
Link to publisher's homepage at http://www.ttp.net/